Level of knowledge and practice of biosafety measures at the Hospital San José, 2016 - Tamariz Chavarria, Frank Dennys (2018)
Objective: To determine the relationship between the level of knowledge and the practice of biosafety measures among the health personnel from the inpatient services of internal medicine, surgery, gynecology and pediatrics of the Hospital San José del Callao. Materials and methods: A quantitative, observational, descriptive, cross-sectional study conducted in a population of 100 health workers from the inpatient services of internal medicine, surgery, gynecology and pediatrics of the Hospital San José from January to June 2016. Results: The level of knowledge among the health personnel ranges from medium (55 %) to low (19 %). These are alarming figures, since the study population works in inpatient departments. The level of practice among the health personnel is good (65 %), but it is at risk of changing to an unfavorable lower level in the inpatient departments. Conclusions: The level of knowledge and practice of biosafety measures among the health personnel showed a significant relationship between both variables (Fisher's exact test p = .000), which means that knowledge about biosafety measures is necessary for a favorable practice, and thus decrease the risk of nosocomial infections.